Alkoxymagnesium supports and methods for their preparation, ziegler-natta catalyst components, catalysts and processes for the polymerization of olefins

CN122958624APending Publication Date: 2026-10-23CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202610534162.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-21
Filing Date
2026-04-21
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0009]鉴于以上分析,本发明旨在提供一种烷氧基镁载体及其制备方法、一种齐格勒-纳塔催化剂组分、一种用于烯烃聚合的催化剂以及一种用于烯烃聚合的方法,用以解决现有技术中烷氧基镁载体颗粒表面形貌不够理想、堆积密度较低的技术问题

Benefits of technology

本发明提供的烷氧基镁载体具有良好的颗粒形态和颗粒表面形貌、更多的小孔径孔、较高的堆积密度和均匀的粒度分布,可用作烯烃聚合反应催化剂的载体。采用本发明提供的烷氧基镁载体制备的烯烃聚合催化剂具有聚合活性高、流动性好的特点,利于提高生产效率,且聚合物细粉含量少、堆积密度大,适用于气相聚合工艺装置生产聚烯烃。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958624A_ABST
    Figure CN122958624A_ABST
Patent Text Reader

Abstract

The application discloses an alkoxy magnesium carrier and a preparation method thereof, a Ziegler-Natta catalyst component, a catalyst and a method for olefin polymerization. A ratio V1 / V2 of a pore volume V1 of pores with a diameter of 7-100 nm in the alkoxy magnesium carrier to a total pore volume V2 of the alkoxy magnesium carrier is (0.20-0.60):1. The alkoxy magnesium carrier has good particle morphology and particle surface morphology, more small-pore-diameter pores, higher bulk density and uniform particle size distribution, and can be used as a carrier of an olefin polymerization reaction catalyst. The olefin polymerization catalyst prepared by using the alkoxy magnesium carrier has the characteristics of high polymerization activity and good fluidity, is beneficial to improving production efficiency, has less polymer fine powder content and high bulk density, and is suitable for producing polyolefin in a gas phase polymerization process device.
Need to check novelty before this filing date? Find Prior Art

Description

Cross-references to related applications

[0001] This application claims the benefit of Chinese Patent Application No. 202510503275.5, filed on April 21, 2025, the contents of which are incorporated herein by reference. Technical Field

[0002] This invention relates to the field of olefin polymerization technology, specifically to an alkoxy magnesium support and its preparation method, a Ziegler-Natta catalyst component, a catalyst for olefin polymerization, and a method for olefin polymerization. Background Technology

[0003] With the increasing demand for polyolefins, the requirements for olefin polymerization catalysts are also becoming more stringent. Currently, the most widely used catalyst is the Ziegler-Natta catalyst supported on magnesium chloride. Methods for preparing catalysts disclosed in patents such as CN85100997A and CN1453298A generally consist of a solid catalyst component composed of magnesium, titanium, and halogen electron-donating organic compounds. However, to meet various performance requirements, such as suitable particle size and shape, uniform particle distribution, minimization of microparticles, and high packing density, as well as high catalyst activity and stereoregularity, it is difficult for a single catalyst to simultaneously satisfy all these demands. Supported catalysts using alkoxymagnesium as a support can exhibit more superior performance and are often used in the development of high-end polypropylene products. The preparation of such catalysts first requires the preparation of high-performance alkoxymagnesium supports. Several patents, such as CN101056894A, CN101027327A, and CN101220113A, mention using alkoxymagnesium as a support to improve various catalyst properties. Therefore, developing high-performance alkoxymagnesium manufacturing technology is a very meaningful endeavor.

[0004] In the preparation of Ziegler-Natta catalysts using alkoxymagnesium as a support, on the one hand, the particle morphology of the support faithfully reflects the particle morphology of the catalyst, while the particle morphology of the polymer replicates the catalyst morphology well; on the other hand, a high packing density of alkoxymagnesium (support) results in better flowability, which is beneficial for improving production efficiency and also facilitates the acquisition of catalysts with high packing density, thereby obtaining polymer powders with high packing density. This is beneficial for increasing the load and production efficiency of the polymerization unit. In summary, particle morphology and packing density are two important parameters for alkoxymagnesium as a Ziegler-Natta catalyst support, and excellent particle morphology and higher packing density are the goals pursued in the preparation of alkoxymagnesium.

[0005] The existing technologies for producing spherical dieoxymagnesium particles mainly include the following methods: First, a method involving the reaction of magnesium with alcohol to produce dieoxymagnesium, followed by mechanical pulverization to adjust particle size; second, a method in which the final magnesium / ethanol ratio is controlled within the range of 9 / 1 to 1 / 15 during the reaction of magnesium with ethanol, and the reaction of ethanol and magnesium occurs intermittently or continuously during ethanol reflux (Japanese Patent Application Laid-Open No. 3-74341); and third, a method involving spray drying an alcoholic solution of carboxylated magnesium. A method for manufacturing round, fine particles by continuing decarboxylation (Japanese Patent Application Laid-Open No. 6-87773); a method for manufacturing particles by reacting metallic magnesium with ethanol under saturated hydrocarbon coexistence conditions (Japanese Patent Publication No. 63-4815); and a method for manufacturing particles by dispersing Mg(OR)2 in R'OH and spray drying the resulting solid particles, suspending them in ROH, and then distilling to remove R'OH, thereby obtaining round particles represented by the chemical formula Mg(OR)(OR') (Japanese Patent Application Laid-Open No. 62-51633).

[0006] In the first method, the particle shape is pulverized and destroyed. To obtain particles with perfect surface morphology and particle size distribution, a low yield is unavoidable. In the second method, although the final magnesium / ethanol addition ratio is specified to be between 9 / 1 and 1 / 15, according to researchers' discussions and experimental results, if the addition ratio is always fixed at 9 / 1, when the reaction rate exceeds 80% during the latter half of the reaction when viscosity rises sharply, the particles will agglomerate without sufficient stirring, resulting in non-uniform spherical particles. If forced stirring is performed, the particle shape will be destroyed (Patent No. 6-239521). On the other hand, if the initial addition ratio is set to 1 / 15, allowing the reaction to occur under conditions of relatively high ethanol content, stirring can proceed smoothly during the final stage of the reaction when viscosity rises, but the resulting particles are not spherical enough and have a low bulk density, failing to obtain particles that meet the requirements. In the third to fifth methods, in addition to Mg and ROH, other raw materials are required, and the operation is also very complicated. Therefore, it can be said that these methods are not advisable for producing the desired particulate matter.

[0007] Moreover, even if alkoxymagnesium carrier particles with a certain degree of sphericity are obtained by using the above method, their surface is still plate-like (CN101415666B, CN102089078A), which will result in a low packing density of the carrier.

[0008] Therefore, developing an alkoxymagnesium support with good surface morphology and high packing density is of great significance for improving catalyst performance and polymer performance. Summary of the Invention

[0009] Based on the above analysis, the present invention aims to provide an alkoxymagnesium support and its preparation method, a Ziegler-Natta catalyst component, a catalyst for olefin polymerization, and a method for olefin polymerization, in order to solve the technical problems of unsatisfactory surface morphology and low packing density of alkoxymagnesium support particles in the prior art.

[0010] To achieve the objective of this invention, a first aspect of this invention provides an alkoxymagnesium support, wherein the ratio of the pore volume V1 of the pores with a diameter of 7 to 100 nm in the alkoxymagnesium support to the total pore volume V2 of the alkoxymagnesium support, V1 / V2, is (0.2 to 0.6):1.

[0011] The second aspect of the present invention provides a method for preparing the alkoxy magnesium support described in the first aspect of the present invention, the method comprising: mixing and reacting a preparation raw material including magnesium powder, alcohol, titanium-containing halide I and optionally a halogenating agent to obtain the alkoxy magnesium support; The halogenating agent is selected from at least one of titanium-containing halides, halogen elements, and titanium-free inorganic halides; Wherein, based on halogen atoms, the ratio of the total molar amount of titanium-containing halide I and the halogenating agent to the molar amount of magnesium powder is 0.005-0.1:1, preferably 0.008-0.08:1; Wherein, based on halogen atoms, the molar ratio of halogen atoms provided by the titanium-containing halide I to the total halogen atoms in the halogenating agent is 0.25-1:1, preferably 0.3-1:1.

[0012] A third aspect of the present invention provides a Ziegler-Natta catalyst component, comprising the following components or reaction products of the following components: i) The alkoxy magnesium support described in the first aspect of the present invention or the alkoxy magnesium support prepared by the preparation method described in the second aspect of the present invention; ii) Titanium-containing halides II; iii) Internal electron donor compounds.

[0013] A fourth aspect of the present invention provides a catalyst for olefin polymerization, the catalyst comprising the following components or reaction products of the following components: a) The Ziegler-Natta catalyst component provided in the third aspect of the present invention; b) Organoaluminum compounds; c) Optional external electron donor compounds.

[0014] The fifth aspect of the present invention provides a method for olefin polymerization, comprising polymerizing olefins under the action of the Ziegler-Natta catalyst component described in the third aspect of the present invention or the catalyst described in the fourth aspect of the present invention.

[0015] The alkoxy magnesium support and its preparation method, the Ziegler-Natta catalyst components, and the catalyst and method for olefin polymerization provided by this invention achieve the following beneficial effects: The alkoxymagnesium support provided by this invention has good particle morphology and surface morphology, more small-diameter pores, high packing density, and uniform particle size distribution, and can be used as a support for olefin polymerization catalysts. Olefin polymerization catalysts prepared using the alkoxymagnesium support provided by this invention exhibit high polymerization activity and good flowability, which is beneficial for improving production efficiency. Furthermore, they have low polymer fine powder content and high packing density, making them suitable for gas-phase polymerization processes to produce polyolefins. Attached Figure Description

[0016] Figure 1 This is a pore volume and pore size distribution diagram of the alkoxymagnesium support prepared in Example 2 of the present invention, tested by mercury intrusion porosimetry. Figure 2 This is a pore volume and pore size distribution diagram of the alkoxymagnesium support prepared in Example 4 of the present invention, tested by mercury intrusion porosimetry. Figure 3 This is a pore volume and pore size distribution diagram of the alkoxymagnesium support prepared in Comparative Example 1 of this invention, tested by mercury intrusion porosimetry. Figure 4 This is a SEM image of the surface of the alkoxymagnesium support prepared in Example 1 of this invention; Figure 5 This is a SEM image of the surface of the alkoxymagnesium support prepared in Comparative Example 1 of this invention. Figure 6 This is an SEM image of the alkoxymagnesium support prepared in Example 1 of this invention. Detailed Implementation

[0017] In this invention, unless otherwise specified, "diameter" refers to the average diameter, and "particle size" refers to the average particle size.

[0018] The first aspect of the present invention provides an alkoxymagnesium support, wherein the ratio of the pore volume V1 of the pores with a diameter of 7 to 100 nm in the alkoxymagnesium support to the total pore volume V2 of the alkoxymagnesium support, V1 / V2, is (0.2 to 0.6):1.

[0019] The alkoxymagnesium support provided by this invention exhibits fusion between the lamellae, and more of the lamellae are stacked in a flat rather than cross-stacked manner. This structure results in better surface morphology of the alkoxymagnesium support particles, and allows for more small-diameter pores and higher packing density, making it suitable as a support for olefin polymerization catalysts.

[0020] Through extensive experimentation, the inventors of this invention discovered that the fusion of lamellae on the surface of the alkoxymagnesium support not only reduces the increase in fine powder caused by lamellae shedding during catalyst preparation, but also increases the proportion of small-diameter pores in the support, reduces the total pore volume, and thus increases the packing density of the support, resulting in a support with excellent morphology and high packing density. This support not only exhibits better flowability, which is beneficial for improving production efficiency, but can also be used to prepare high-performance Ziegler-Natta catalysts.

[0021] In this invention, the inventors discovered that after the lamellar portions on the surface of the alkoxymagnesium support fuse to form pores with a diameter of 7-100 nm, the support, when prepared into a catalyst, can significantly reduce the risk of the active centers formed by the lamellar crystals breaking during the catalytic polymerization of olefins while maintaining the catalyst activity, and can effectively reduce the content of fine powder in the polymer.

[0022] In this invention, the ratio V1 / V2 of the pore volume V1 of the 7-100 nm diameter pores in the alkoxymagnesium support to the total pore volume V2 of the alkoxymagnesium support is (0.2-0.6):1, for example, it can be 0.2:1, 0.21:1, 0.22:1, 0.23:1, 0.24:1, 0.25:1, 0.26:1, 0.27:1, 0.28:1, 0.29:1, 0.3:1, 0.31:1, 0.32:1, 0.33:1, 0.34:1, 0.35:1, 0. 36:1, 0.37:1, 0.38:1, 0.39:1, 0.4:1, 0.41:1, 0.42:1, 0.43:1, 0.44:1, 0.45:1, 0.46:1, 0.47:1, 0.48:1, 0.49:1, 0.5:1, 0.51:1, 0.52:1, 0.53:1, 0.54:1, 0.55:1, 0.56:1, 0.57:1, 0.58:1, 0.59:1, 0.6:1, and the range of any two values.

[0023] According to some embodiments of the present invention, the total pore volume V2 of the alkoxymagnesium support is 0.6–1 cm. 3 / g.

[0024] In this invention, when the total pore volume V2 of the alkoxymagnesium support meets the above-mentioned range, it indicates that the alkoxymagnesium support has a high packing density, which is beneficial to improving the packing density of the catalyst and the polymer.

[0025] It should be noted that the "total pore volume" in this invention includes the pore volume of pores with a diameter of 7 nm to 10 μm.

[0026] In this invention, the total pore volume V2 of the alkoxymagnesium support is 0.6–1 cm.3 / g, for example, can be 0.6 cm 3 / g, 0.61 cm 3 / g, 0.62 cm 3 / g, 0.63 cm 3 / g, 0.64 cm 3 / g, 0.65 cm 3 / g, 0.66 cm 3 / g, 0.67 cm 3 / g, 0.68 cm 3 / g, 0.69 cm 3 / g, 0.7 cm 3 / g, 0.71 cm 3 / g, 0.72 cm 3 / g, 0.73 cm 3 / g, 0.74 cm 3 / g, 0.75 cm 3 / g, 0.76 cm 3 / g, 0.77 cm 3 / g, 0.78 cm 3 / g, 0.79 cm 3 / g, 0.8 cm 3 / g, 0.81 cm 3 / g, 0.82 cm 3 / g, 0.83 cm 3 / g, 0.84 cm 3 / g, 0.85 cm 3 / g, 0.86 cm 3 / g, 0.87 cm 3 / g, 0.88 cm 3 / g, 0.89 cm 3 / g, 0.9 cm 3 / g, 0.91 cm 3 / g, 0.92 cm 3 / g, 0.93 cm 3 / g, 0.94 cm 3 / g, 0.95 cm 3 / g, 0.96 cm 3 / g, 0.97 cm 3 / g, 0.98 cm 3 / g, 0.99 cm 3 / g, 1 cm 3 / g, and a range consisting of any two values.

[0027] According to some embodiments of the present invention, the alkoxymagnesium support contains titanium.

[0028] According to some embodiments of the present invention, the titanium element is derived from titanium-containing halides.

[0029] According to some embodiments of the present invention, the titanium-containing halide includes those with the general formula TiX. m (OR) 4-m Compounds and / or their derivatives, wherein X is a halogen, preferably chlorine, bromine or iodine; R is a C1 to C2 compound. 20 The hydrocarbon group, preferably a C2 to C4 hydrocarbon group; m is an integer from 1 to 4.

[0030] According to some embodiments of the present invention, the titanium-containing halide includes at least one of titanium tetrahalide, titanium alkoxytrihalide, titanium dialkoxydihalide, and titanium trialkoxyhalide.

[0031] According to some embodiments of the present invention, the titanium-containing halide includes at least one of titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, titanium monochlorotriethoxy, titanium dichlorodiethoxy, and titanium trichloroethoxy.

[0032] According to some embodiments of the present invention, the titanium-containing halide is titanium tetrachloride.

[0033] According to some embodiments of the present invention, the titanium content in the alkoxymagnesium support is 0.01–2 wt%, for example, it can be 0.01 wt%, 0.02 wt%, 0.03 wt%, 0.04 wt%, 0.05 wt%, 0.06 wt%, 0.07 wt%, 0.08 wt%, 0.09 wt%, 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1 wt%, 1.1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, 1.5 wt%, 1.6 wt%, 1.7 wt%, 1.8 wt%, 1.9 wt%, 2 wt%, and any two of these values, preferably 0.03–1 wt%, more preferably 0.05–0.5 wt%.

[0034] According to some embodiments of the present invention, the alkoxymagnesium carrier is a particulate.

[0035] According to some embodiments of the present invention, the particle size of the alkoxymagnesium support is 10-80 μm, for example, it can be 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, and any range of two values, preferably 20-50 μm.

[0036] According to some embodiments of the present invention, the particle size distribution SPAN of the alkoxymagnesium support is ≤0.9, for example, it can be 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, 0.1, and any two of these values, preferably 0.6 to 0.9.

[0037] When the particle size and particle size distribution SPAN of the alkoxymagnesium carrier described in this invention meet the above-mentioned range, it indicates that the alkoxymagnesium carrier provided by this invention has good particle morphology and uniform particle size distribution.

[0038] According to some embodiments of the present invention, the specific surface area of ​​the alkoxymagnesium support is 10 to 200 m² / g, for example, it can be 10 m² / g, 20 m² / g, 30 m² / g, 40 m² / g, 50 m² / g, 60 m² / g, 70 m² / g, 80 m² / g, 90 m² / g, 100 m² / g, 110 m² / g, 120 m² / g, 130 m² / g, 140 m² / g, 150 m² / g, 160 m² / g, 170 m² / g, 180 m² / g, 190 m² / g, 200 m² / g, and any range of two values, preferably 50 to 180 m² / g, more preferably 80 to 130 m² / g.

[0039] According to some embodiments of the present invention, the repose angle of the alkoxymagnesium support is ≤42°, for example, it can be 42°, 41°, 40°, 39°, 38°, 37°, 36°, 35°, 34°, 33°, 32°, 31°, 30°, 29°, 28°, 27°, 26°, 25°, and any range of two values, preferably 30 to 40°.

[0040] In this invention, when the angle of repose of the alkoxymagnesium support meets the above-mentioned range, it indicates that the alkoxymagnesium support has excellent flowability.

[0041] According to some embodiments of the present invention, the bulk density of the alkoxymagnesium support is ≥0.3 g / cm³. 3, for example, it can be 0.3 m² / g, 0.31 m² / g, 0.32 m² / g, 0.33 m² / g, 0.34 m² / g, 0.35 m² / g, 0.36 m² / g, 0.37m² / g, 0.38 m² / g, 0.39 m² / g, 0.4 m² / g, 0.41 m² / g, 0.42 m² / g, 0.43 m² / g, 0.44 m² / g, 0.45 m² / g, 0.46 m² / g, 0.47 m² / g, 0.48 m² / g, 0.49 m² / g, 0.5 m² / g, 0.51 m² / g, 0.52 m² / g, 0.53 m² / g, 0.54 m² / g, 0.55 The m² / g, and the range of any two values, is preferably 0.3–0.5 g / cm³. 3 .

[0042] In this invention, when the packing density of the alkoxymagnesium support is within the above-mentioned range, it is more beneficial to increase the packing density of the catalyst and the polymer.

[0043] In one specific embodiment of the present invention, the ratio of the pore volume V1 of the pores with a diameter of 7-100 nm in the alkoxymagnesium support to the total pore volume V2 of the alkoxymagnesium support, V1 / V2, is (0.2-0.6):1, and the total pore volume V2 of the alkoxymagnesium support is 0.6-1 cm. 3 / g; the bulk density of the alkoxymagnesium support is ≥0.3g / cm³. 3 .

[0044] A second aspect of the present invention provides a method for preparing the above-mentioned alkoxy magnesium support, comprising: mixing and reacting a preparation raw material including magnesium powder, alcohol, titanium-containing halide I and optionally a halogenating agent to obtain the alkoxy magnesium support; The halogenating agent is selected from at least one of titanium-containing halides, halogen elements, and titanium-free inorganic halides; The ratio of the total molar amount of halogen atoms to the molar amount of magnesium powder is 0.005-0.1:1. In this case, the molar ratio of halogen atoms provided by the titanium-containing halide I to the total halogen atoms is 0.25-1:1, based on halogen atoms.

[0045] The method for preparing alkoxymagnesium supports provided by this invention involves a direct reaction of metallic magnesium, an alcohol, and optionally a halogenating agent to produce spherical microparticle alkoxymagnesium supports. The preparation method is simple and easy to operate. During the preparation process, a titanium-containing halide I is added to fuse the lamellar crystals on the surface of the alkoxymagnesium support. This fusion of surface lamellar crystals increases the proportion of small-diameter pores in the pore structure of the support surface, thereby reducing the total pore volume and improving the packing density. Furthermore, the fusion of surface lamellar crystals makes the support surface smoother, resulting in fewer inter-carrier gaps during carrier stacking, thus increasing the packing density and improving the carrier's fluidity.

[0046] In this invention, the "total halogen atoms" includes the sum of the molar amount of halogen atoms provided by the titanium-containing halide I and the molar amount of halogen atoms in the halogenating agent.

[0047] According to some embodiments of the present invention, the molar ratio of total halogen atoms to the molar ratio of magnesium powder is (0.005-0.1):1, for example, 0.005:1, 0.006:1, 0.007:1, 0.008:1, 0.009:1, 0.01:1, 0.012:1, 0.015:1, 0.02:1, 0.022:1, 0.025:1, 0.03:1, 0.031:1, 0.032:1, 0.035:1, 0.038:1, 0.04:1, 0.041:1, 0.043:1, 0.044:1, 0.045:1, 0.047:1, 0.05: 1. The range of any two values, including 0.052:1, 0.054:1, 0.056:1, 0.058:1, 0.06:1, 0.062:1, 0.064:1, 0.066:1, 0.068:1, 0.07:1, 0.072:1, 0.074:1, 0.076:1, 0.078:1, 0.08:1, 0.082:1, 0.084:1, 0.086:1, 0.088:1, 0.09:1, 0.092:1, 0.094:1, 0.096:1, 0.098:1, 0.01:1, and preferably (0.008-0.08):1.

[0048] According to some embodiments of the present invention, the molar ratio of halogen atoms provided by the titanium-containing halide I to the total halogen atoms is 0.25-1:1, based on halogen atoms. For example, it can be 0.25:1, 0.3:1, 0.35:1, 0.4:1, 0.45:1, 0.5:1, 0.55:1, 0.6:1, 0.65:1, 0.7:1, 0.75:1, 0.8:1, 0.85:1, 0.9:1, 0.95:1, 1:1, and any range of two values, preferably 0.3-1:1.

[0049] According to some embodiments of the present invention, the titanium-containing halide I comprises the general formula TiX m (OR) 4-m Compounds and / or their derivatives, wherein X is a halogen, preferably chlorine, bromine or iodine; R is a C1 to C2 compound. 20 The hydrocarbon group, preferably a C2 to C4 hydrocarbon group; m is an integer from 1 to 4.

[0050] According to some embodiments of the present invention, the titanium-containing halide I includes at least one of titanium tetrahalide, titanium alkoxytrihalide, titanium dialkoxydihalide, and titanium trialkoxyhalide.

[0051] According to some embodiments of the present invention, the titanium-containing halide I includes at least one of titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, titanium monochlorotriethoxy, titanium dichlorodiethoxy, and titanium trichloroethoxy.

[0052] According to some embodiments of the present invention, the titanium-containing halide I is titanium tetrachloride.

[0053] According to some embodiments of the present invention, the titanium-containing halide I can be used alone as a halogenating agent to prepare the alkoxy magnesium support, or it can be added simultaneously with a halogenating agent (e.g., at least one of titanium-containing halides, halogens, and titanium-free inorganic halides) to prepare the alkoxy magnesium support, or it can be added separately from a halogenating agent (e.g., at least one of titanium-containing halides, halogens, and titanium-free inorganic halides) to prepare the alkoxy magnesium support. There are no specific limitations on its usage.

[0054] According to some embodiments of the present invention, the titanium halide comprises the general formula TiX m (OR) 4-m Compounds and / or their derivatives, wherein X is a halogen, preferably chlorine, bromine or iodine; R is a C1 to C2 compound. 20 The hydrocarbon group, preferably a C2 to C4 hydrocarbon group; m is an integer from 1 to 4.

[0055] According to some embodiments of the present invention, the titanium-containing halide includes at least one of titanium tetrahalide, titanium alkoxytrihalide, titanium dialkoxydihalide, and titanium trialkoxyhalide.

[0056] According to some embodiments of the present invention, the titanium-containing halide includes at least one of titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, titanium monochlorotriethoxy, titanium dichlorodiethoxy, and titanium trichloroethoxy.

[0057] According to some embodiments of the present invention, the titanium halide is titanium tetrachloride.

[0058] In some embodiments of the present invention, the halide as a halogenating agent may be the same as or different from the titanium-containing halide I.

[0059] According to some embodiments of the present invention, the halogen is selected from at least one of iodine, bromine, and chlorine.

[0060] According to some embodiments of the present invention, the titanium-free inorganic halide is selected from at least one of magnesium chloride, magnesium bromide, magnesium iodide, calcium chloride, calcium bromide, calcium iodide, mercuric chloride, mercuric bromide, and mercuric iodide.

[0061] In one specific embodiment of the present invention, when the halogenating agent is only a titanium-containing halide, and the type of halogenating agent is the same as that of titanium-containing halide I, that is, titanium-containing halide I can also be used as a halogenating agent to complete the preparation of the alkoxy magnesium support, in this case, the molar ratio of halogen atoms provided by titanium-containing halide I to total halogen atoms is 1:1 based on halogen atoms.

[0062] According to some embodiments of the present invention, the average particle size of the magnesium powder is less than or equal to 360 μm, for example, it can be 360 ​​μm, 350 μm, 340 μm, 330 μm, 320 μm, 310 μm, 300 μm, 290 μm, 280 μm, 270 μm, 260 μm, 250 μm, 240 μm, 230 μm, 220 μm, 210 μm, 200 μm, 190 μm, 180 μm, 170 μm, 160 μm, 150 μm, 140 μm, 130 μm, 120 μm, 110 μm, 100 μm, 90 μm, 80 μm, 70 μm, 60 μm, 50 μm, 40 μm, 30 μm, 20 μm, and any range of two values, preferably 100 μm to 300 μm.

[0063] The magnesium powder used in this invention can be of any shape, such as granules, ribbons, or powder, provided that its reactivity is good. To ensure that the average particle size of the generated alkoxymagnesium support remains between 10 μm and 80 μm and that the particle morphology is excellent, the magnesium powder is preferably spherical with an average particle size of less than 360 μm, and more preferably between 100 μm and 300 μm, thus maintaining relatively uniform reactivity. Furthermore, the surface of the magnesium powder is not particularly limited, but the formation of a hydroxide or other coating on the surface of the magnesium powder will slow down the reaction; therefore, magnesium powder without a hydroxide or other coating on its surface is preferred.

[0064] According to some embodiments of the present invention, the alcohol is selected from at least one of straight-chain monohydric alcohols, branched-chain monohydric alcohols, straight-chain polyhydric alcohols, and branched-chain polyhydric alcohols.

[0065] According to some embodiments of the present invention, the alcohol includes at least one selected from methanol, ethanol, n-propanol, n-butanol, n-pentanol, n-hexanol, n-heptanol, n-octanol, n-nonanol, n-decanol, 2-propanol, 2-butanol, 2-pentanol, 2-hexanol, 2-heptanol, 2-octanol, 2-nonanol, 2-decanol, 2-ethylbutanol, 2-ethylhexanol, 4-methyl-2-pentanol, 3,3,5-trimethylpentanol, 4-methyl-3-heptanol, benzyl alcohol, 2-phenylethanol, 1-phenyl-1-propanol, ethylene glycol, and glycerol.

[0066] According to some embodiments of the present invention, the alcohol is ethanol or a mixture of ethanol and isooctanol or a mixture of ethanol and isopropanol, wherein the ethanol content in the mixture is 80wt% to 99wt%.

[0067] This invention does not particularly limit the water content of the alcohol; however, to obtain good performance of the alkoxymagnesium support, a lower water content is preferred. According to some embodiments of the invention, the water content of the alcohol is ≤1000 ppm, preferably ≤200 ppm.

[0068] According to some embodiments of the present invention, the molar ratio of the alcohol to magnesium powder is (2-50):1, for example 2.5:1, 3:1, 3.2:1, 3.5:1, 3.7:1, 4:1, 4.2:1, 4.4:1, 4.6:1, 4.9:1, 5:1, 5.3:1, 5.6:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 8.8:1, 9:1, 9.5:1, 10:1, 10.5:1, 11:1, 11.3:1, 11.6:1, 12:1, 12.5:1, 13:1, 14:1, 14.5:1, 15:1, 16:1, 17:1, 17.5:1, 18:1, and any range of two values, preferably (2.5-18):1.

[0069] According to some embodiments of the present invention, the reaction conditions include: being carried out under a protective gas atmosphere (e.g., nitrogen, argon), with nitrogen being preferred in the present invention.

[0070] According to some embodiments of the present invention, the order of addition of each component in the reaction can be determined as needed; specifically, there are no particular restrictions on the method of adding the halogenating agent. It can be added directly to magnesium powder and ethanol in liquid form to start the reaction process, or the halogenating agent can be added dropwise during the heating of magnesium powder and alcohol solution for reaction preparation; preferably, the halogenating agent is added dropwise during the heating of magnesium powder and alcohol solution for reaction preparation.

[0071] Furthermore, for the addition of magnesium powder, alcohols, and titanium halide I, the reactants can be added all at once initially, or they can be added in stages. Adding reactants in stages prevents the instantaneous generation of large amounts of hydrogen gas and the resulting droplets of alcohols or halogens. From a safety perspective, this method is preferred. The number of stages can be determined based on the size of the reaction vessel and the amount of each material used.

[0072] The reaction temperature of this invention can be carried out from 0°C to the reflux temperature of the reaction system. Small changes in reaction pressure will cause changes in the reflux temperature; the higher the selected reaction temperature, the faster the reaction proceeds. The reaction temperature can also be varied during the reaction, and the particle size and morphology can be altered by selecting the appropriate reaction temperature. The preferred reaction temperature of this invention is the reflux temperature of the reaction system.

[0073] This invention determines the extent of the reaction by observing the amount of hydrogen emitted during the reaction, and the reaction time is usually 2 to 30 hours.

[0074] According to an embodiment of the present invention, the reaction product is subjected to drying treatment.

[0075] According to an embodiment of the present invention, after the reaction, the product can be washed with the alcohol and / or a mixture of alcohols used to prepare the alkoxymagnesium support; it can also be washed with the organic solvent used in the reaction; depending on the specific circumstances, washing may be optional, and the method and number of washing treatments are not particularly limited.

[0076] A third aspect of the present invention provides a Ziegler-Natta catalyst component, comprising the following components or reaction products of the following components: i) The alkoxy magnesium support described in the first aspect of the present invention or the alkoxy magnesium support prepared by the preparation method described in the second aspect; ii) Titanium-containing halides II; iii) Internal electron donor compounds.

[0077] According to some embodiments of the present invention, generally, in order to obtain a high isotactic propylene polymer, at least one optional internal electron donor compound needs to be added during the preparation of the catalyst component, depending on the needs of the actual application.

[0078] In this invention, there is no particular limitation on the internal electron donor compound; any internal electron donor compound commonly used in the art and applicable to Ziegler-Natta catalyst components can be selected.

[0079] Preferably, the internal electron donor compound is selected from one or more of carboxylic acid ester electron donor compounds, diol ester compounds, 1,3-diether compounds, succinate compounds, and cyanosuccinate compounds.

[0080] More preferably, the carboxylic acid ester electron-donating compound is selected from benzoic acid monoester compounds and / or phthalic acid ester compounds represented by Formula I. (Formula I) In Formula I, R1 and R2 may be the same or different, and each is independently selected from substituted or unsubstituted C1-C8 alkyl groups, C3-C6 alkyl groups. 10 cycloalkyl or C6-C 20 The aromatic group; R3 to R6 may be the same or different, each independently selected from hydrogen, halogen, C1 to C4 alkyl or C1 to C4 alkoxy; more preferably, at least three of R3 to R6 are hydrogen; even more preferably, the carboxylic acid ester electron donor compound is selected from at least one of di-n-butyl phthalate, diisobutyl phthalate, diethyl phthalate, dipentyl phthalate, dioctyl phthalate, methyl benzoate, ethyl benzoate, propyl benzoate, isopropyl benzoate, butyl benzoate and isobutyl benzoate.

[0081] More preferably, the internal electron donor compound is selected from diisobutyl phthalate (DIBP), di-n-butyl phthalate, 9,9-bis(methoxymethyl)fluorene, 2-isopropyl-2-isopentyl-1,3-dimethoxypropane, 3,5-heptanediol dibenzoate, 2,4-pentanediol dibenzoate, diethyl 2,3-diisopropylsuccinate, and diethyl 2-cyano-2,3-diisopropylsuccinate.

[0082] According to some embodiments of the present invention, the titanium-containing halide II comprises the general formula TiX' n (OR') 4-n Compounds and / or their derivatives, wherein X' is a halogen, preferably chlorine, bromine or iodine; R' is a C1 to C2 compound. 20 The hydrocarbon group, n is an integer from 1 to 4; preferably, the titanium-containing halide II includes at least one of titanium tetrahalide, titanium alkoxy trihalide, titanium dialkoxy dihalide and titanium trialkoxy halide; more preferably, the titanium-containing halide II includes at least one of titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, titanium monochlorotriethoxy, titanium dichlorodiethoxy and titanium trichloroethoxy.

[0083] According to some embodiments of the present invention, the molar ratio of the internal electron-donating compound to the alkoxymagnesium support is (0.005–10):1, for example, 0.005:1, 0.006:1, 0.007:1, 0.008:1, 0.009:1, 0.01:1, 0.03:1, 0.05:1, 0.08:1, 0.1:1, 0.11:1, 0.12:1, 0.14:1, 0.16:1, 0.2:1, 0.22:1, 0.26:1, 0.3:1, 0.33:1, 0.38:1, 0.4:1, 0.45:1, 0.5:1. The range of values ​​is 0.6:1, 0.7:1, 0.78:1, 0.8:1, 0.85:1, 0.9:1, 0.96:1, 1:1, 1.1:1, 1.15:1, 1.22:1, 1.3:1, 1.36:1, 1.4:1, 1.45:1, 1.5:1, 1.6:1, 1.67:1, 1.75:1, 1.8:1, 1.83:1, 1.85:1, 1.9:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, and any two values ​​within a range, preferably (0.01~2):1.

[0084] According to some embodiments of the present invention, the molar ratio of the titanium-containing halide II to the alkoxymagnesium support is (0.5 to 100):1, for example 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 2:1, 4:1, 5:1, 7:1, 9:1, 10:1, 12:1, 15:1, 16:1, 20:1, 23:1, 25:1, 26:1, 28:1, 30:1, 33:1, 35:1, 38:1, 40:1, 41:1, 42:1, 45:1, 48:1, 50:1, 55:1, 60:1, 70:1, 75:1, 80:1, 85:1, 90:1, 95:1, 100:1, and any range of two values, preferably (1 to 50):1.

[0085] According to some embodiments of the present invention, the titanium content in the Ziegler-Natta catalyst component is 1.5wt% to 3.5wt%, preferably 2.1wt% to 3.1wt%.

[0086] The present invention also provides a method for preparing the Ziegler-Natta catalyst component, wherein the reaction conditions for the alkoxy magnesium support, titanium-containing halide II and internal electron donor compound include: a reaction temperature of -40℃ to 200℃, preferably -20℃ to 150℃, and a reaction time of 1 min to 20 h, preferably 5 min to 8 h.

[0087] A fourth aspect of the present invention provides a catalyst for olefin polymerization, the catalyst comprising the following components or reaction products of the following components: a) The Ziegler-Natta catalyst component as described in the third aspect of the present invention; b) Organoaluminum compounds; c) Optional external electron donor compounds.

[0088] According to embodiments of the present invention, there are no particular limitations on the organoaluminum compound, and any alkylaluminum compound commonly used in the art for use in Ziegler-Natta type catalysts may be selected.

[0089] According to some embodiments of the present invention, the organoaluminum compound has the general formula AlR 1 k X 1 3-k , where R 1 Selected from hydrogen, C1 to C 20 Alkyl groups, C6-C 20 aryl; X 1 The halogen is k; k is an integer from 1 to 3; preferably, the organoaluminum compound is selected from at least one of trimethylaluminum, triethylaluminum, triisobutylaluminum, trioctylaluminum, diethylaluminum hydrogen, diisobutylaluminum hydrogen, diethylaluminum chloride, diisobutylaluminum chloride, sesquiethylaluminum chloride, and diethylaluminum chloride.

[0090] According to embodiments of the present invention, optionally, the external electron donor compound refers to a catalyst system for olefin polymerization that may or may not contain an external electron donor compound. In this invention, there is no particular limitation on the external electron donor compound; any commonly used external electron donor compound in the art suitable for use in Ziegler-Natta type catalysts can be selected.

[0091] According to some embodiments of the present invention, the general formula of the external electron donor compound is R. 2 p R 3 q Si(OR 4 ) 4-p-q , where R 2 and R 3 Whether the elements are the same or different, they are each independently selected from halogens, hydrogen atoms, and C1 to C2 atoms. 20 Alkyl groups, C3-C 20 cycloalkyl, C6-C 20 aryl and C1-C 20 Any one of the haloalkyl groups, R 4 Selected from C1 to C 20 Alkyl groups, C3-C 20 cycloalkyl, C6-C 20aryl and C1-C 20 The alkyl halogroup is selected from any one of the following: p and q are integers from 0 to 3, and p + q < 4; preferably, the external electron donor compound is selected from at least one of the following: trimethylmethoxysilane, trimethylethoxysilane, trimethylphenoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, methyl tert-butyldimethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, dicyclohexyldimethoxysilane, diisopropyldimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, vinyltrimethoxysilane, cyclohexylmethyldimethoxysilane, dicyclopentyldimethoxysilane, 2-ethylpiperidinyl-2-tert-butyldimethoxysilane, (1,1,1-trifluoro-2-propyl)-2-ethylpiperidinyldimethoxysilane, and (1,1,1-trifluoro-2-propyl)-methyldimethoxysilane.

[0092] According to some embodiments of the present invention, the molar ratio of aluminum in the organoaluminum compound to titanium in the Ziegler-Natta catalyst component is (5-5000):1, for example, it can be 5:1, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1, 150:1, 200:1, 250:1, 300:1, 350:1, 400:1, 450:1, 500... The range of values ​​is 1, 550:1, 600:1, 650:1, 700:1, 750:1, 800:1, 850:1, 900:1, 950:1, 1000:1, 1500:1, 2000:1, 2500:1, 3000:1, 3500:1, 4000:1, 4500:1, 5000:1, and any two values, preferably (20 to 1000):1, more preferably (50 to 500):1.

[0093] According to some embodiments of the present invention, the molar ratio of aluminum in the organoaluminum compound to silicon in the external electron donor compound is (0.1–500):1, for example, it can be 0.1:1, 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 20:1, 30:1, 40:1, 50. The range of values ​​is 1, 60:1, 70:1, 80:1, 90:1, 100:1, 120:1, 140:1, 160:1, 180:1, 200:1, 220:1, 240:1, 260:1, 280:1, 300:1, 350:1, 400:1, 450:1, 500:1, and any two values, preferably (1 to 300):1, more preferably (3 to 100):1.

[0094] The fifth aspect of the present invention provides a method for olefin polymerization, comprising polymerizing olefins under the action of the above-described Ziegler-Natta catalyst component or the above-described catalyst.

[0095] The olefin polymerization method of the present invention can be used for homopolymerization of olefins, or for copolymerization of multiple olefins.

[0096] According to some embodiments of the present invention, the olefin has the general formula CH2=CHR. 5 , where R 5 It is hydrogen or a C1-C6 alkyl group.

[0097] According to some embodiments of the present invention, the olefin is at least one selected from ethylene, propylene, 1-n-butene, 1-n-pentene, 1-n-hexene, 1-n-octene and 4-methyl-1-pentene.

[0098] According to the olefin polymerization method of the present invention, there are no particular limitations on the olefin polymerization conditions, and conventional conditions in the art can be selected; there are no particular limitations on the amount of catalyst used, and the amounts of various catalysts used in prior art olefin polymerization can be selected.

[0099] According to some embodiments of the present invention, the polymerization temperature is 0℃ to 150℃, preferably 60℃ to 130℃; the time is 0.1h to 5h, preferably 0.5h to 4h; and the pressure is 0.01MPa to 10MPa, preferably 0.5MPa to 5MPa.

[0100] The present invention will be further described below with reference to embodiments. However, the present invention is not limited to these embodiments.

[0101] Unless otherwise specified in the embodiments of this invention, the conditions shall be performed according to conventional conditions or the conditions recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0102] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0103] In this embodiment of the invention, the heating process is not specifically limited, and any known method can be used for heating, such as slow, stepwise, rapid, or programmed heating. The specific heating method can be adjusted according to the specific formula, contact temperature, etc.

[0104] According to the preparation method of the present invention, under the same conditions, different heating processes will affect the particle morphology, particle size distribution, catalyst activity and polymer properties of the final catalyst. Specifically, a slower heating process can obtain better particle morphology, while a faster heating rate will lead to poorer particle shape and decreased sphericity.

[0105] In this embodiment of the invention, the magnesium powder used was purchased from Tangshan Weihou Magnesium Powder Co., Ltd., and the particle size was 100μm to 300μm; In this embodiment of the invention, the particle size and particle size distribution of the alkoxy magnesium support were measured using the Malvern Mastersizer™ 3000 n-hexane dispersant laser diffraction method, wherein the SPAN value = (D90-D10) / D50.

[0106] In this embodiment of the invention, the bulk density (BD) of the alkoxymagnesium support and the bulk density (BD) of the polymer are both determined by the method of weight of loose solids per unit volume.

[0107] In this embodiment of the invention, the pore volume of the alkoxymagnesium support was tested using mercury intrusion porosimetry (instrument model: PoreMaster GT60), obtaining a d~dV / dlog(d) curve. The integral of the curve corresponding to d = 7~100 nm is V1, and the integral over the entire curve is denoted as V2, where d is the pore diameter (μm). The testing method includes: weighing the sample and placing it into a sample tube; placing the sample tube in a low-pressure station and evacuating it to 20 mmHg for 3 minutes; injecting mercury; and performing low-pressure and high-pressure tests (pressure 0.2-30000 PSI).

[0108] In this embodiment of the invention, the specific surface area of ​​the alkoxymagnesium support was measured using the nitrogen adsorption method (instrument model: Autosorb 6100) to determine the BET specific surface area. The test conditions included: degassing temperature of 100℃ and degassing time of 12h.

[0109] In this embodiment of the invention, the titanium atom content in the carrier was tested by ICP-MS using a Thermo Fisher Scientific iCAP TQ triple quadrupole inductively coupled plasma mass spectrometer. Specifically, the test parameters were: incident power: 1550W, cooling gas flow rate: 14L / min, auxiliary gas flow rate: 0.8L / min, nebulizing gas flow rate: 0.7L / min, and reaction gas (O2) flow rate: 0.3mL / min.

[0110] In this embodiment of the invention, the polymerization activity of the Ziegler-Natta catalyst component is calculated by dividing the total mass of the polymer powder produced by polymerization by the mass of the catalyst used in polymerization.

[0111] In this embodiment of the invention, the proportion of fine powder is calculated by dividing the mass of polymer particles with a particle size less than 0.180 mm by the total polymer mass.

[0112] In this embodiment of the invention, the melt index (MI) of the polymer was determined using an XRZ-00 melt indexer according to the method specified in GB / T3682-2000. The test conditions included: a temperature of 230°C and a load of 2.16 kg.

[0113] In this embodiment of the invention, the isotactic index of the polymer is tested as follows: 2 grams of dry polymer sample is placed in an extractor and extracted with boiling heptane for 6 hours, and the residue is dried to constant weight.

[0114] Isotacticity calculation formula: Isotacticity II = Mass of extracted polymer / 2 × 100%.

[0115] In this embodiment of the invention, the SEM image of the alkoxymagnesium support was taken using an S-4800 scanning electron microscope.

[0116] In this embodiment of the invention, the angle of repose of the alkoxymagnesium support was tested using an angle of repose tester, and the test method referred to GB / T 11986-1989. The angle of repose of the alkoxymagnesium support can be used to evaluate the flowability of the support; the smaller the angle of repose test result, the better the flowability of the support.

[0117] Example 1 This embodiment provides an alkoxy magnesium carrier.

[0118] The preparation method is as follows: In a reactor equipped with a stirrer, a reflux condenser, a thermometer, and a burette were installed. After thorough purging with nitrogen, 320 mL of ethanol with a water content of less than 200 ppm was added to the reactor, followed by 15 g of magnesium powder and 0.57 g of titanium tetrachloride. The mixture was stirred and the reaction was initiated. After 15 min of reaction, another 15 g of magnesium powder was added, and the mixture was stirred and heated until the reflux temperature of the reaction system was reached. The reaction was continued until it was complete, i.e., no more hydrogen was emitted. The mixture was then washed, separated, and dried to obtain the alkoxymagnesium support.

[0119] This embodiment further provides a Ziegler-Natta catalyst component.

[0120] The preparation steps are as follows: In a 300 mL reactor that has been repeatedly purged with high-purity nitrogen, 10 mL of toluene and 90 mL of titanium tetrachloride were added. The mixture was cooled to -15 °C, and 10 g of alkoxymagnesium support particles prepared in Example 1, along with a suspension prepared from 50 mL of toluene and 1.2 mL of di-n-butyl phthalate (DNBP), were added. The mixture was then slowly heated to 120 °C and held at that temperature for 2 hours. The liquid was then filtered clean. Next, a mixture of 30 mL of titanium tetrachloride and 120 mL of toluene was added, and the mixture was heated to 110 °C. 1.5 mL of DNBP was added dropwise, and the mixture was stirred for 1 hour. The liquid was then filtered clean again. The mixture of 30 mL of titanium tetrachloride and 120 mL of toluene was added, and the mixture was heated to 110 °C and stirred for 1 hour. This process was repeated twice. The liquid was filtered off, and the resulting solid was washed four times with 150 mL of hexane in an oil bath at 60 °C. The liquid was then filtered off and the solid powder was dried to obtain the Ziegler-Natta catalyst component. The titanium content in the Ziegler-Natta catalyst component is shown in Table 2.

[0121] This embodiment further provides a method for propylene polymerization.

[0122] The aggregation steps are as follows: In a 5-liter autoclave, nitrogen gas was used to purge the mixture at 70°C for 1 hour. Then, at room temperature, 5 mL of a triethylaluminum hexane solution (0.5 mmol / mL), 1 mL of a cyclohexylmethyldimethoxysilane (CHMMS) hexane solution (0.10 mmol / mL), 10 mL of anhydrous hexane, and 10 mg of the Ziegler-Natta catalyst component prepared in Example 1 were introduced into the nitrogen gas stream. The autoclave was then shut off, and 1 L of hydrogen (under standard conditions) and 2 L of liquid propylene were introduced. The temperature was raised to 70°C within 10 minutes with stirring, and the polymerization reaction was carried out at 70°C for 1 hour. After stirring was stopped, unpolymerized propylene monomers were removed, and the propylene polymer was collected.

[0123] Example 2 This embodiment provides an alkoxy magnesium carrier.

[0124] The preparation method is as follows: In a reactor equipped with a stirrer, a reflux condenser, a thermometer, and a burette were installed. After thorough purging with nitrogen, 310 mL of ethanol with a water content of less than 200 ppm and 10 mL of isooctanol with a water content of less than 200 ppm were added to the reactor. Then, 15 g of magnesium powder, 0.19 g of titanium tetrachloride, and 1 g of elemental iodine were added and stirred to initiate the reaction. After reacting for 15 minutes, another 15 g of magnesium powder was added, and the mixture was stirred and heated until the reflux temperature of the reaction system was reached. The reaction was continued until it was complete, i.e., no more hydrogen was emitted. Then, the mixture was washed, separated, and dried to obtain the alkoxymagnesium support.

[0125] This embodiment further provides a Ziegler-Natta catalyst component.

[0126] The preparation steps are the same as in Example 1, except that the alkoxymagnesium support particles prepared in Example 2 are used instead of the alkoxymagnesium support particles prepared in Example 1 to obtain the Ziegler-Natta catalyst component.

[0127] This embodiment further provides a method for propylene polymerization.

[0128] The polymerization steps were the same as in Example 1, except that the Ziegler-Natta catalyst component prepared in Example 2 was used instead of the Ziegler-Natta catalyst component prepared in Example 1, and the propylene polymer was collected.

[0129] Example 3 This embodiment provides an alkoxy magnesium carrier.

[0130] The preparation method is as follows: In a reactor equipped with a stirrer, a reflux condenser, a thermometer, and a burette are installed. After thorough purging with nitrogen, 315 mL of ethanol with a water content of less than 200 ppm and 5 mL of isooctanol with a water content of less than 200 ppm are added to the reactor, followed by 15 g of magnesium powder. The mixture is stirred and the reaction proceeds. After 15 min of reaction, another 15 g of magnesium powder and 0.57 g of titanium tetrachloride are added, and the mixture is stirred and heated until the reflux temperature of the reaction system is reached. The reaction is continued until it is complete, i.e., no more hydrogen is emitted. The mixture is then washed, separated, and dried to obtain the alkoxymagnesium support.

[0131] This embodiment further provides a Ziegler-Natta catalyst component.

[0132] The preparation steps are the same as in Example 1, except that the alkoxymagnesium support particles prepared in Example 3 are used instead of the alkoxymagnesium support particles prepared in Example 1, the 1.2 mL DNBP used to prepare the suspension is replaced with 1.2 mL of diisobutyl phthalate (DIBP), and the 1.5 mL DNBP added is replaced with 1.5 mL DIBP, to obtain the Ziegler-Natta catalyst component.

[0133] This embodiment further provides a method for propylene polymerization.

[0134] The polymerization steps were the same as in Example 1, except that the Ziegler-Natta catalyst component prepared in Example 3 was used instead of the Ziegler-Natta catalyst component prepared in Example 1, and the propylene polymer was collected.

[0135] Example 4 This embodiment provides an alkoxy magnesium carrier.

[0136] The preparation method is as follows: In a reactor equipped with a stirrer, a reflux condenser, a thermometer, and a burette were installed. After thorough purging with nitrogen, 320 mL of ethanol with a water content of less than 200 ppm was added to the reactor, followed by 15 g of magnesium powder and 0.40 g of trichloroethoxytitanium (Ti(CH2CH3O)Cl3). The mixture was stirred and the reaction was initiated. After reacting for 15 min, another 15 g of magnesium powder and 0.40 g of trichloroethoxytitanium were added, and the mixture was stirred and heated until the reflux temperature of the reaction system was reached. The reaction was continued until it was complete, i.e., no more hydrogen was emitted. The mixture was then washed, separated, and dried to obtain the alkoxymagnesium support.

[0137] This embodiment further provides a Ziegler-Natta catalyst component.

[0138] The preparation steps are the same as in Example 1, except that the alkoxymagnesium support particles prepared in Example 4 are used instead of the alkoxymagnesium support particles prepared in Example 1 to obtain the Ziegler-Natta catalyst component.

[0139] This embodiment further provides a method for propylene polymerization.

[0140] The polymerization steps were the same as in Example 1, except that the Ziegler-Natta catalyst component prepared in Example 4 was used instead of the Ziegler-Natta catalyst component prepared in Example 1, and the propylene polymer was collected.

[0141] Example 5 This embodiment provides an alkoxy magnesium carrier.

[0142] The preparation method is as follows: In a reactor equipped with a stirrer, a reflux condenser, a thermometer, and a burette were installed. After thorough purging with nitrogen, 320 mL of ethanol with a water content of less than 200 ppm was added to the reactor, followed by 15 g of magnesium powder and 0.29 g of titanium tetrachloride. The mixture was stirred and the reaction was initiated. After reacting for 15 min, another 15 g of magnesium powder and 0.29 g of titanium tetrachloride were added, and the mixture was stirred and heated until the reflux temperature of the reaction system was reached. The reaction was continued until it was complete, i.e., no more hydrogen was emitted. The mixture was then washed, separated, and dried to obtain the alkoxymagnesium support.

[0143] This embodiment further provides a Ziegler-Natta catalyst component.

[0144] The preparation steps are the same as in Example 1, except that the alkoxymagnesium support particles prepared in Example 5 are used instead of the alkoxymagnesium support particles prepared in Example 1 to obtain the Ziegler-Natta catalyst component.

[0145] This embodiment further provides a method for propylene polymerization.

[0146] The polymerization steps were the same as in Example 1, except that the Ziegler-Natta catalyst component prepared in Example 5 was used instead of the Ziegler-Natta catalyst component prepared in Example 1, and the propylene polymer was collected.

[0147] Example 6 This embodiment provides an alkoxy magnesium carrier.

[0148] The preparation method is as follows: In a reactor equipped with a stirrer, a reflux condenser, a thermometer, and a burette were installed. After thorough purging with nitrogen, 320 mL of ethanol with a water content of less than 200 ppm was added to the reactor, followed by 15 g of magnesium powder, 0.16 g of titanium tetrachloride, and 1.08 g of elemental iodine. The mixture was stirred and the reaction was initiated. After 15 min of reaction, another 15 g of magnesium powder was added, and the mixture was stirred and heated until the reflux temperature of the reaction system was reached. The reaction was continued until it was complete, i.e., no more hydrogen gas was emitted. The mixture was then washed, separated, and dried to obtain the alkoxymagnesium support.

[0149] This embodiment further provides a Ziegler-Natta catalyst component.

[0150] The preparation steps are the same as in Example 1, except that the alkoxymagnesium support particles prepared in Example 6 are used instead of the alkoxymagnesium support particles prepared in Example 1 to obtain the Ziegler-Natta catalyst component.

[0151] This embodiment further provides a method for propylene polymerization.

[0152] The polymerization steps were the same as in Example 1, except that the Ziegler-Natta catalyst component prepared in Example 6 was used instead of the Ziegler-Natta catalyst component prepared in Example 1, and the propylene polymer was collected.

[0153] Example 7 This embodiment provides an alkoxy magnesium carrier.

[0154] The preparation method is as follows: In a reactor equipped with a stirrer, a reflux condenser, a thermometer, and a burette were installed. After thorough purging with nitrogen, 320 mL of ethanol with a water content of less than 200 ppm was added to the reactor, followed by 15 g of magnesium powder and 0.57 g of titanium tetrachloride. The mixture was stirred and the reaction was initiated. After reacting for 15 minutes, another 15 g of magnesium powder and 0.57 g of titanium tetrachloride were added and the reaction was initiated again. The temperature was increased until the reflux temperature of the reaction system was reached. The reaction was continued until it was complete, i.e., no more hydrogen was emitted. The mixture was then washed, separated, and dried to obtain the alkoxymagnesium support.

[0155] This embodiment further provides a Ziegler-Natta catalyst component.

[0156] The preparation steps are the same as in Example 1, except that the alkoxymagnesium support particles prepared in Example 7 are used instead of the alkoxymagnesium support particles prepared in Example 1 to obtain the Ziegler-Natta catalyst component.

[0157] This embodiment further provides a method for propylene polymerization.

[0158] The polymerization steps were the same as in Example 1, except that the Ziegler-Natta catalyst component prepared in Example 7 was used instead of the Ziegler-Natta catalyst component prepared in Example 1, and the propylene polymer was collected.

[0159] Comparative Example 1 This comparative example provides an alkoxy magnesium support.

[0160] The preparation method is as follows: In a reactor equipped with a stirrer, a reflux condenser, a thermometer, and a burette were installed. After thorough purging with nitrogen, 320 mL of ethanol with a water content of less than 200 ppm was added to the reactor, followed by 15 g of magnesium powder and 1.5 g of elemental iodine. The mixture was stirred and the reaction was initiated. After 15 min of reaction, another 15 g of magnesium powder was added, and the mixture was stirred and heated until the reflux temperature of the reaction system was reached. The reaction was continued until it was complete, i.e., no more hydrogen gas was emitted. The mixture was then washed, separated, and dried to obtain the alkoxymagnesium support.

[0161] This comparative example further provides a Ziegler-Natta catalyst component.

[0162] The preparation steps are the same as in Example 1, except that the alkoxymagnesium support particles prepared in Comparative Example 1 are used instead of the alkoxymagnesium support particles prepared in Example 1 to obtain the Ziegler-Natta catalyst component.

[0163] This comparative example further provides a method for propylene polymerization.

[0164] The polymerization steps were the same as in Example 1, except that the Ziegler-Natta catalyst component prepared in Comparative Example 1 was used instead of the Ziegler-Natta catalyst component prepared in Example 1, and the propylene polymer was collected.

[0165] Comparative Example 2 This comparative example provides an alkoxy magnesium support.

[0166] The preparation method is as follows: In a reactor equipped with a stirrer, a reflux condenser, a thermometer, and a burette were installed. After thorough purging with nitrogen, 310 mL of ethanol with a water content of less than 200 ppm and 10 mL of isooctanol with a water content of less than 200 ppm were added to the reactor. Then, 15 g of magnesium powder, 1.0 g of elemental iodine, and 0.5 mL of tetraethyl titanate were added and stirred to initiate the reaction. After reacting for 15 min, another 15 g of magnesium powder was added, and the mixture was stirred and heated until the reflux temperature of the reaction system was reached. The reaction was continued until it was complete, i.e., no more hydrogen was emitted. Then, the mixture was washed, separated, and dried to obtain the alkoxymagnesium support.

[0167] This comparative example further provides a Ziegler-Natta catalyst component.

[0168] The preparation steps are the same as in Example 2, except that the alkoxymagnesium support particles prepared in Comparative Example 2 are used instead of the alkoxymagnesium support particles prepared in Example 2 to obtain the Ziegler-Natta catalyst component.

[0169] This comparative example further provides a method for propylene polymerization.

[0170] The polymerization steps were the same as in Example 2, except that the Ziegler-Natta catalyst component prepared in Comparative Example 2 was used instead of the Ziegler-Natta catalyst component prepared in Example 2, and the propylene polymer was collected.

[0171] Comparative Example 3 This comparative example provides an alkoxy magnesium support.

[0172] The preparation method is as follows: In a reactor equipped with a stirrer, a reflux condenser, a thermometer, and a burette are installed. After thorough purging with nitrogen, 300 mL of ethanol with a water content of less than 200 ppm and 20 mL of toluene with a water content of less than 200 ppm are added to the reactor. Then, 15 g of magnesium powder and 1.5 g of elemental iodine are added, and the mixture is stirred and the reaction is initiated. After 15 minutes of reaction, another 15 g of magnesium powder is added, and the mixture is stirred and heated until the reflux temperature of the reaction system is reached. The reaction is continued until it is complete, i.e., no more hydrogen is emitted. Then, the mixture is washed, separated, and dried to obtain the alkoxymagnesium support.

[0173] This comparative example further provides a Ziegler-Natta catalyst component.

[0174] The preparation steps are the same as in Example 2, except that the alkoxymagnesium support particles prepared in Comparative Example 3 are used instead of the alkoxymagnesium support particles prepared in Example 2 to obtain the Ziegler-Natta catalyst component.

[0175] This comparative example further provides a method for propylene polymerization.

[0176] The polymerization steps were the same as in Example 2, except that the Ziegler-Natta catalyst component prepared in Comparative Example 3 was used instead of the Ziegler-Natta catalyst component prepared in Example 2, and the propylene polymer was collected.

[0177] Comparative Example 4 This embodiment provides an alkoxy magnesium carrier.

[0178] The preparation method is as follows: In a reactor equipped with a stirrer, a reflux condenser, a thermometer, and a burette were installed. After thorough purging with nitrogen, 346 mL of ethanol with a water content of less than 200 ppm was added to the reactor, followed by 32 g of magnesium powder and 0.30 g of titanium tetrachloride. The mixture was stirred and the temperature was increased until the reflux temperature of the reaction system was reached. The reaction was continued until it was complete, i.e., no more hydrogen was emitted. The mixture was then washed, separated, and dried to obtain the alkoxymagnesium support.

[0179] This comparative example further provides a Ziegler-Natta catalyst component.

[0180] The preparation steps are the same as in Example 2, except that the alkoxymagnesium support particles prepared in Comparative Example 4 are used instead of the alkoxymagnesium support particles prepared in Example 2 to obtain the Ziegler-Natta catalyst component.

[0181] This comparative example further provides a method for propylene polymerization.

[0182] The polymerization steps were the same as in Example 2, except that the Ziegler-Natta catalyst component prepared in Comparative Example 4 was used instead of the Ziegler-Natta catalyst component prepared in Example 2, and the propylene polymer was collected.

[0183] Comparative Example 5 This embodiment provides an alkoxy magnesium carrier.

[0184] The preparation method is as follows: In a reactor equipped with a stirrer, a reflux condenser, a thermometer, and a burette were installed. After thorough purging with nitrogen, 320 mL of ethanol with a water content of less than 200 ppm was added to the reactor, followed by 15 g of magnesium powder, 0.11 g of titanium tetrachloride, and 1.21 g of elemental iodine. The mixture was stirred and the reaction was initiated. After 15 min of reaction, another 15 g of magnesium powder was added, and the mixture was stirred and heated until the reflux temperature of the reaction system was reached. The reaction was continued until it was complete, i.e., no more hydrogen gas was emitted. The mixture was then washed, separated, and dried to obtain the alkoxymagnesium support.

[0185] This embodiment further provides a Ziegler-Natta catalyst component.

[0186] The preparation steps are the same as in Example 1, except that the alkoxymagnesium support particles prepared in Comparative Example 5 are used instead of the alkoxymagnesium support particles prepared in Example 1 to obtain the Ziegler-Natta catalyst component.

[0187] This embodiment further provides a method for propylene polymerization.

[0188] The polymerization steps were the same as in Example 1, except that the Ziegler-Natta catalyst component prepared in Comparative Example 5 was used instead of the Ziegler-Natta catalyst component prepared in Example 1, and the propylene polymer was collected.

[0189] To further illustrate the present invention, the raw material ratios for preparing the alkoxy magnesium support in Examples 1-6 and Comparative Examples 1-5 are summarized in Table 1 below; Table 1

[0190] To further illustrate the advancements of the present invention, the performance parameters of the alkoxy magnesium support, Ziegler-Natta catalyst components, and polymers prepared in Examples 1-4 and Comparative Examples 1-4 are statistically summarized in Tables 2-3 below.

[0191] Table 2

[0192] Table 3

[0193] As can be seen from the data in Tables 1-2, the support prepared using titanium halide as an initiator in this invention has a higher proportion of small-pore (7-100 nm) pores, a relatively low total pore volume, and a higher packing density. Furthermore, the fusion of lamellar crystals on the support surface (such as...) Figure 4 (As shown) This makes the carrier surface smoother, resulting in fewer inter-carrier gaps during carrier stacking, which is beneficial for increasing the carrier packing density; it also improves the carrier's fluidity. In Comparative Example 2, a certain amount of titanate ester compound was added during the preparation of the alkoxymagnesium carrier, resulting in a carrier containing 0.06% titanium. However, the titanate ester compound cannot act as an initiator in the reaction process and cannot affect the pore structure of the carrier or increase its packing density. In Comparative Example 3, a certain amount of toluene was added to ethanol during the preparation of the alkoxymagnesium carrier. Although this increased the carrier packing density, the increase was due to the presence of toluene in the carrier. This toluene is difficult to remove during the carrier drying process, leading to an increased packing density, but it does not affect the pore distribution or structure of the carrier.

[0194] In Comparative Example 4, the total amount of halogenating agent used in the preparation process was low, which made it difficult for the lamellar crystals on the surface of the prepared alkoxymagnesium support to fully fuse, resulting in a low pore size ratio of the support and an insufficiently smooth surface with poor fluidity, leading to a low bulk density of the support.

[0195] In the preparation of the alkyl magnesium support in Comparative Example 5, the content of titanium halide in the halogenating agent was low, which could not fully exert the modification effect of titanium halide on the lamellar crystals on the support surface. This resulted in a decrease in the pore size ratio and packing density of the support, and the support surface was not smooth enough with poor fluidity.

[0196] As can be seen from the data in Table 2-3, when using the Ziegler-Natta catalyst component prepared with the alkoxy magnesium support provided by the present invention for propylene polymerization, the polymerization activity is high, the content of fine polymer powder is low, and the resulting polymer has a high packing density. This is beneficial for the long-term stable application of the catalyst component in large-scale propylene polymerization plants, and it has broad prospects.

[0197] Figure 1 and Figure 2 It can be seen that the pore volume distribution of the alkoxymagnesium supports prepared in Examples 2 and 4 has a higher proportion of pore volume in the range of 7-100 nm, and there are obvious peaks in this range. Figure 3 It can be seen that the pore volume distribution of the alkoxymagnesium support prepared in Comparative Example 1 is mainly between 100 nm and 1 μm, and the proportion of pore volume below 100 nm to the total pore volume is significantly smaller.

[0198] Figure 4 and Figure 5 As can be seen, compared with Comparative Example 1, the alkoxymagnesium support prepared in Example 1 has obvious fusion of lamellae, more lamellae are stacked flat rather than cross-stacked, the pore size is smaller, and the surface is smoother.

[0199] Figure 6 This indicates that the alkoxymagnesium support prepared in Example 1 also has a smooth surface, which is beneficial to improving the flowability of the support.

[0200] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. An alkoxymagnesium support, characterized in that, The ratio of the pore volume V1 of the 7-100 nm diameter pores in the alkoxymagnesium support to the total pore volume V2 of the alkoxymagnesium support, V1 / V2, is (0.2-0.6):

1.

2. The alkoxymagnesium support according to claim 1, characterized in that, The total pore volume V2 of the alkoxymagnesium support is 0.6–1 cm. 3 / g; And / or, the alkoxymagnesium support contains titanium; preferably, the titanium is derived from a titanium-containing halide; preferably, the titanium content in the alkoxymagnesium support is 0.01–2 wt%, more preferably 0.03–1 wt%, and even more preferably 0.05–0.5 wt%. And / or, the alkoxymagnesium support is particulate; preferably, the particle size of the alkoxymagnesium support is 10-80 μm, more preferably 20-50 μm; preferably, the particle size distribution SPAN of the alkoxymagnesium support is ≤0.9, more preferably 0.6-0.9; And / or, the specific surface area of ​​the alkoxymagnesium support is 10-200 m² / g, preferably 50-180 m² / g, more preferably 80-130 m² / g; And / or, the bulk density of the alkoxymagnesium support is ≥0.3 g / cm³. 3 Preferably, it is 0.3–0.5 g / cm³. 3 ; And / or, the angle of repose of the alkoxymagnesium support is ≤42°, preferably 30-40°.

3. A method for preparing an alkoxymagnesium support as described in claim 1 or 2, characterized in that, The preparation method includes: mixing and reacting raw materials including magnesium powder, alcohol, titanium-containing halide I and optionally a halogenating agent to obtain the alkoxy magnesium support; The halogenating agent is selected from at least one of titanium-containing halides, halogen elements, and titanium-free inorganic halides; The ratio of the total molar amount of halogen atoms to the molar amount of magnesium powder is 0.005-0.1:1, preferably 0.008-0.08:1; Specifically, based on halogen atoms, the molar ratio of halogen atoms provided by the titanium-containing halide I to the total halogen atoms is 0.25-1:1, preferably 0.3-1:

1.

4. The preparation method according to claim 3, characterized in that, The titanium-containing halide I includes those with the general formula TiX. m (OR) 4-m Compounds and / or their derivatives, wherein X is a halogen, preferably chlorine, bromine or iodine; R is a C1 to C2 compound. 20 The hydrocarbon group, where m is an integer from 1 to 4; Preferably, the titanium-containing halide I includes at least one of titanium tetrahalide, titanium alkoxytrihalide, titanium dialkoxydihalide, and titanium trialkoxyhalide; more preferably, the titanium-containing halide I includes at least one of titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, titanium monochlorotriethoxy, titanium dichlorodiethoxy, and titanium trichloroethoxy. And / or, the halogen is selected from at least one of iodine, bromine, and chlorine; And / or, the titanium-free inorganic halide is selected from at least one of magnesium chloride, magnesium bromide, magnesium iodide, calcium chloride, calcium bromide, calcium iodide, mercuric chloride, mercuric bromide, and mercuric iodide.

5. The preparation method according to claim 3 or 4, characterized in that, The average particle size of the magnesium powder is ≤360μm, preferably 100μm~300μm; And / or, the alcohol is selected from at least one of straight-chain monohydric alcohols, branched-chain monohydric alcohols, straight-chain polyhydric alcohols, and branched-chain polyhydric alcohols; preferably, the alcohol includes at least one of methanol, ethanol, n-propanol, n-butanol, n-pentanol, n-hexanol, n-heptanol, n-octanol, n-nonanol, n-decanol, 2-propanol, 2-butanol, 2-pentanol, 2-hexanol, 2-heptanol, 2-octanol, 2-nonanol, 2-decanol, 2-ethylbutanol, 2-ethylhexanol, 4-methyl-2-pentanol, 3,3,5-trimethylpentanol, 4-methyl-3-heptanol, benzyl alcohol, 2-phenylethanol, 1-phenyl-1-propanol, ethylene glycol, and glycerol; more preferably, the alcohol is a mixture of ethanol and isooctanol or a mixture of ethanol and isopropanol, wherein the ethanol content in the mixture is 80wt% to 99wt%. And / or, the water content of the alcohol is ≤1000ppm, preferably ≤200ppm; And / or, the molar ratio of the alcohol to the magnesium powder is (2-50):1, preferably (2.5-18):

1.

6. A Ziegler-Natta catalyst component, characterized in that, Includes the following components or the reaction products of the following components: i) The alkoxy magnesium support according to claim 1 or 2, or the alkoxy magnesium support prepared by the preparation method according to any one of claims 3-5; ii) Titanium-containing halides II; iii) Internal electron donor compounds.

7. The Ziegler-Natta catalyst component according to claim 6, characterized in that, The internal electron donor compound is selected from one or more of carboxylic acid ester electron donor compounds, diol ester compounds, 1,3-diether compounds, succinate compounds, and cyanosuccinate compounds; Preferably, the carboxylic acid ester electron-donating compound is selected from benzoic acid monoester compounds and / or phthalic acid ester compounds represented by Formula I. (Formula I) In Formula I, R1 and R2 may be the same or different, and each is independently selected from substituted or unsubstituted C1-C8 alkyl groups, C3-C6 alkyl groups. 10 cycloalkyl or C6-C 20 The aromatic group; R3-R6 may be the same or different, each independently selected from hydrogen, halogen, C1-C4 alkyl or C1-C4 alkoxy; more preferably, at least three of R3-R6 are hydrogen; even more preferably, the carboxylic acid ester electron donor compound is selected from at least one of di-n-butyl phthalate, diisobutyl phthalate, diethyl phthalate, dipentyl phthalate, dioctyl phthalate, methyl benzoate, ethyl benzoate, propyl benzoate, isopropyl benzoate, butyl benzoate and isobutyl benzoate; Preferably, the internal electron donor compound is selected from diisobutyl phthalate, di-n-butyl phthalate, 9,9-bis(methoxymethyl)fluorene, 2-isopropyl-2-isopentyl-1,3-dimethoxypropane, 3,5-heptanediol dibenzoate, 2,4-pentanediol dibenzoate, diethyl 2,3-diisopropylsuccinate, and diethyl 2-cyano-2,3-diisopropylsuccinate. And / or, the titanium-containing halide II comprises those with the general formula TiX' n (OR') 4-n Compounds and / or their derivatives, wherein X' is a halogen, preferably chlorine, bromine or iodine; R' is a C1 to C2 compound. 20 The hydrocarbon group, n is an integer from 1 to 4; preferably, the titanium-containing halide II includes at least one of titanium tetrahalide, titanium alkoxy trihalide, titanium dialkoxy dihalide and titanium trialkoxy halide; more preferably, the titanium-containing halide II includes at least one of titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, titanium monochlorotriethoxy, titanium dichlorodiethoxy and titanium trichloroethoxy. And / or, the molar ratio of the internal electron donor compound to the alkoxymagnesium support is (0.005-10):1, preferably (0.01-2):1; And / or, the molar ratio of the titanium-containing halide II to the alkoxymagnesium support is (0.5-100):1, preferably (1-50):1; And / or, the titanium content in the Ziegler-Natta catalyst component is 1.5wt% to 3.5wt%.

8. A catalyst for olefin polymerization, characterized in that, The catalyst comprises the following components or the reaction products of the following components: a) The Ziegler-Natta catalyst component as described in claim 6 or 7; b) Organoaluminum compounds; c) Optional external electron donor compounds.

9. The catalyst according to claim 8, characterized in that, The general formula of the organoaluminum compound is AlR 1 k X 1 3-k , where R 1 Selected from hydrogen, C1-C20 alkyl groups, and C6-C20 aryl groups; X 1 The halogen is k; k is an integer from 1 to 3; preferably, the organoaluminum compound is selected from at least one of trimethylaluminum, triethylaluminum, triisobutylaluminum, trioctylaluminum, diethylaluminum hydrogen, diisobutylaluminum hydrogen, diethylaluminum chloride, diisobutylaluminum chloride, sesquiethylaluminum chloride, and diethylaluminum chloride. And / or, the general formula of the external electron donor compound is R 2 p R 3 q Si(OR 4 ) 4-p-q , where R 2 and R 3 Whether the elements are the same or different, they are each independently selected from halogens, hydrogen atoms, and C1 to C2 atoms. 20 Alkyl groups, C3-C 20 cycloalkyl, C6-C 20 aryl and C1-C 20 Any one of the haloalkyl groups, R 4 Selected from C1 to C 20 Alkyl groups, C3-C 20 cycloalkyl, C6-C 20 aryl and C1-C 20 The alkyl halogroup is selected from any one of the following: p and q are integers from 0 to 3, and p+q<4; preferably, the external electron donor compound is selected from at least one of the following: trimethylmethoxysilane, trimethylethoxysilane, trimethylphenoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, methyl tert-butyldimethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, dicyclohexyldimethoxysilane, diisopropyldimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, vinyltrimethoxysilane, cyclohexylmethyldimethoxysilane, dicyclopentyldimethoxysilane, 2-ethylpiperidinyl-2-tert-butyldimethoxysilane, (1,1,1-trifluoro-2-propyl)-2-ethylpiperidinyldimethoxysilane, and (1,1,1-trifluoro-2-propyl)-methyldimethoxysilane; And / or, the molar ratio of aluminum in the organoaluminum compound to titanium in the Ziegler-Natta catalyst component is (5-5000):1, preferably (20-1000):1, more preferably (50-500):1; And / or, the molar ratio of aluminum in the organoaluminum compound to silicon in the external electron donor compound is (0.1-500):1, preferably (1-300):1, more preferably (3-100):

1.

10. A method for olefin polymerization, characterized in that, This includes polymerizing olefins under the action of the Ziegler-Natta catalyst component of claim 6 or 7 or the catalyst of claim 8 or 9; Preferably, the olefin has the general formula CH2=CHR. 5 , where R 5 It is hydrogen or a C1-C6 alkyl group; more preferably, the olefin is at least one selected from ethylene, propylene, 1-n-butene, 1-n-pentene, 1-n-hexene, 1-n-octene and 4-methyl-1-pentene; Preferably, the polymerization temperature is 0℃~150℃, more preferably 60℃~130℃; the time is 0.1h~5h, more preferably 0.5~4h; and the pressure is 0.01MPa~10MPa, more preferably 0.5MPa~5MPa.

Citation Information

Patent Citations

  • Method of preparation of spherical support for olefin polymerization catalyst

    CN101027327A

  • Catalyst for propylene polymerization and the method of propylene polymerization using the catalyst

    CN101056894A

  • Polythene catalyst and method for preparing the same

    CN101220113A

  • Dialkoxymagnesium granular material and method for synthesis of the same

    CN101415666B

  • Method for controlling size of spherical carrier for olefin polymerization catalyst

    CN102089078A